Trade Contracts in the Hands of AI, Who is Responsible? - Tutik Asmorowati; Mokh. Thoif (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The increasing integration of artificial intelligence (AI) in the formation and execution of trade contracts has introduced profound legal complexities within Indonesia’s civil law system. While the Indonesian Electronic Information and Transactions Law (ITE Law) and Government Regulation No. 71 of 2019 (PP PSTE) confer legal validity on electronic contracts and the use of electronic agents, they offer limited doctrinal guidance on liability attribution when AI operates autonomously. This normative legal study investigates how existing Indonesian legal instruments, particularly the Civil Code, can accommodate AI-mediated contractual performance and explores who should bear legal responsibility in cases of breach, error, or non-performance. Employing statutory, conceptual, case, and comparative approaches, the research constructs a proximate responsibility model grounded in civil liability theory, legal subject theory, and risk allocation principles. Findings indicate that Indonesia’s anthropocentric notion of legal subjectivity limits current liability frameworks, creating ambiguity where AI operates independently. The study proposes doctrinal reforms, including statutory amendments, administrative oversight, sector-specific regulations, and a multi-stakeholder liability model. These recommendations aim to ensure legal certainty, contractual fairness, and consumer protection in an increasingly automated commercial environment. The study contributes original doctrinal insights by systematically linking Indonesian civil law to emerging international AI governance models and offering a structured pathway for legal reform responsive to technological disruption.